Early Phosphatidylinositol 3-Kinase/Akt Pathway Activation Limits Poliovirus-Induced JNK-Mediated Cell Death - Autret, Arnaud (American Society for Microbiology (ASM), 2008)
Poliovirus (PV)-induced apoptosis seems to play a major role in tissue injury in the central nervous system (CNS). We have previously shown that this process involves PV-induced Bax-dependent mitochondrial dysfunction mediated by early JNK activation in IMR5 neuroblastoma cells. We showed here that PV simultaneously activates the phosphatidylinositol 3-kinase (PI3K)/Akt survival signaling pathway in these cells, limiting the extent of JNK activation and thereby cell death. JNK inhibition is associated with PI3K-dependent negative regulation of the apoptosis signal-regulating kinase 1, which acts upstream from JNK in PV-infected IMR5 cells. In poliomyelitis, this survival pathway may limit the spread of PV-induced damage in the CNS.